Outcome and One Year Follow-up of Intra-arterial Staphylokinase in 191 Patients with Peripheral Arterial Occlusion - Heymans, Stephane; Vanderschueren, Steven; Verhaeghe, Raymond; Stockx, Luc; Lacroix, Hendrik; Nevelsteen, André; Laroche, Yves; Collen, Désiré (Thrombosis and Haemostasis, 2000)
Wild-type or equipotent variants of recombinant staphylokinase (rSak) were given intra-arterially (as a 2 mg bolus injection followed by an infusion of 1 mg/h or 0.5 mg/h overnight, with concomitant heparin [1000 IU/h]) to 191 patients of less than 80 years (62 ± 1 years, mean ± SEM), with a peripheral arterial occlusion (PAO) of less than 120 days (mean 14 ± 1 days, median 11 days, 5 to 95 percentiles 3 to 30 days). Ninety nine patients presented with acute or subacute ischemia, 57 with severe claudication, 33 with chronic rest pain and 2 with gangrene. Occlusion occurred in 122 native arteries and in 69 grafts. Revascularization was complete in 83 percent (158/191), partial in 13 percent (24/191) and absent in 4 percent (7/191) after administration of 12 ± 0.5 mg rSak over 14 ± 0.7 h. Complete revascularization of acute occlusions of popliteal or more distal arteries was less frequent (60 percent, 15/25) than of acute occlusions of more proximal native arteries (95 percent, 37/39, p <0.001) or grafts (89 percent, 50/56, p = 0.005). Additional endovascular procedures were performed in 47 percent and subsequent elective bypass surgery in 23 percent of patients. Major bleeding occurred in 12 percent (23/191), one month mortality was 3.1 percent (6/191) and one year mortality was 6.9 percent (12/174). However, four patients (2.1 percent) had an intracranial bleeding following therapy: a 85 year old woman with severe diabetic arteriopathy, who was included in violation of the protocol, a 79 and a 74-year-old woman and a 74-year-old man, all with severe hypertension and limb threatening ischemia; these four patients died within two months after treatment. Amputations were performed within the first year in 16 of 162 surviving patients (9.8 percent): in 7 percent (7/96) with an occluded native artery and 14 percent (9/66) with an occluded graft (p = 0.19). No significant difference in lysis rate, one month mortality or one year amputation-free survival was observed in occlusions of recent onset (<14 days, n = 126) as compared to occlusions of longer duration (<14 days, n = 65). Treatment was interrupted prematurely in 4 patients because of a suspected allergic reaction. Fibrinogen levels remained unaffected during treatment (3.3 ± 0.1 g/l before vs. 3.3 ± 0.1 g/l after infusion, n = 167).In conclusion, rSak appears to be a highly effective thrombolytic agent in patients with PAO, resulting in a low one month mortality (3.1 percent) and a high one year amputation free survival (84 percent), with an acceptable incidence of major bleedings, but with occasional fatal intracranial hemorrhages.
Keywords: Staphylokinase; thrombolysis; peripheral vascular disease; plasminogen activators